Rekonstruksi Budaya Hukum Berdimensi Pancasila dalam Upaya Penegakan Hukum di Indonesia - Anajeng Esri Edhi Mahanani (Fakultas Hukum Universitas Surabaya, 2019)
The issue of weak law enforcement in Indonesia is indeed not a new issue, but this issue has still not been resolved until now. The purpose of this discussion is to find the ideal law enforcement model in accordance with national values. First, the discussion of this article will look at the correlation between law enforcement and the legal system which ultimately can be concluded that law enforcement always correlates with the optimal legal system at work, namely legal structure, legal substance and legal culture. One of these sub-systems does not work properly and optimally, so the ideals of ideal law enforcement will not be achieved easily. This paper then discusses the hypotheses of the three law enforcement subsystems, in fact that legal culture being the main factor, namely the determination of other subsystems. A good legal culture will encourage legal structures to form substantive norms and implement legislation with responsibility. Next discussed is the determination of the reconstruction model of legal culture that has the Pancasila dimension. Pancasila in this case becomes a filter in reconstruction the legal culture in order to enforce the law in accordance with the original noble values ​​of the Indonesian nation. Bad habits in the community should not be interpreted as a noble culture of the nation. Keywords: “legal structure”, “legal substance”, “legal culture”, “reconstruction”, “Pancasila”